THE RELATIONSHIP BETWEEN ADDICTION TO PLAYING ONLINE GAMES AND THE PSYCHOSOCIAL DEVELOPMENT OF SCHOOL-AGE CHILDREN AT STATE ELEMENTARY SCHOOL 21 JALAN KERETA API IN 2024 - SAFITRI, AULIA; YUSRA, REZKI YETI; AULIA, FAJRI FEBRINI (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2024)
Psychosocial development in school-age children is the change and stability of emotions and social relationships that can influence cognitive and physical functioning. Factors that affect the psychosocial development of school-age children are nutrition, genetics, economics, and the environment. One of these environmental factors is playing online games with friends. This research aimed to determine the relationship between online gaming addiction and the psychosocial development of school children in State elementary school 21 Jalan Kereta Api. This type of quantitative research used a descriptive-analytical design with a cross-sectional approach. The research was conducted from 15 July to 19 July 2024 at State elementary school 21 Jalan Kereta Api. The research sample was determined to be 43 people. Sampling was done using convenience sampling. Statistical tests were conducted using univariate analysis and bivariate analysis using Chi-Square. The research results showed that half of the respondents, namely 24 (55.8%), were addicted to playing online games and the psychosocial development of school-age children was in the good category, namely 17 (39.5%). The results of this research showed that there was a relationship between addiction to online games and psychosocial development of school children with p-value = 0.012 (p-value < α 0.05) at State elementary school 21 Jalan Kereta Api in 2024. Conclusion, The less students are addicted to playing online games, the better the psychosocial development of these students. Suggestion, This research is expected to serve as a guide for teachers to recognize the signs or negative effects of online game addiction on students' psychosocial development, and for teachers to help reduce online game addiction so that they can overcome students' psychosocial development.